Cuando Antioquia se volvió Medellín, 1905-1950. Los perfiles de la inmigración pueblerina hacia Medellín (2011)
ABSTRACT: In the half century elapsed between 1905 and 1951, Medellín went from being a large town to becoming a city around which the economic, social, political and cultural matters of the Antioquia region revolved. No doubt, the migration of villagers to the city contributed significantly to this growth. Why do villagers migrate to the city? The objective of this article is to answer that question by stressing the importance of villagers in the consolidation and strengthening of Medellín as the second most important city in Colombia. Follow-up of student enrolment, résumés of Coltejer workers, stories of entrepreneurs and politicians from Antioquia, and marriage registrations was carried out in order to obtain statistics regarding the villagers who migrated to the city for economic, political, work, or education reasons. This made it possible to establish place of origin, migration factors, and permanence in the city.